Estimasi Produktivitas Padi Level Kecamatan di Kabupaten Tulungagung Menggunakan Geoadditive SAE - Garinca Firgiana Santoso; Siti Muchlisoh (Jurnal Aplikasi Statistika & Komputasi Statistik, 2020)
Paddy productivity data is one of the benchmarks for the government to audit the success of local food self-sufficiency program. Paddy productivity data is used to calculate paddy production in a region. Local government needs paddy production data at sub-district level to identify local food supply for the population. However, the estimation of paddy production data at sub-district level is constrained by the absence of paddy productivity data at sub-district level. BPS presents the data at regency level only. This research aims to estimate paddy productivity at sub-district level in Tulungagung Regency in 2019 using geoadditive small area estimation, evaluate the accuracy of the estimation using Root Mean Square Error (RMSE) and Relative Standard Error (RSE), and identify the rice surplus-deficit at sub-district level. Analysis method being used was inferential analysis using indirect estimation by geoadditive SAE. The estimation showed that the highest paddy productivity was in Pucanglaban Sub-district (8,8648 ton/ha), while the lowest paddy productivity in Pagerwojo Sub-district (3,6576 ton/ha). The use of geoadditive SAE gave more precision to the estimation because it produced smaller RMSE and RSE than direct estimation method. The estimation also showed that major sub-districts of Tulungagung Regency experienced surplus in rice during 2019, but there were also six sub-districts which suffered deficit in rice.